Nomen est omen medical and pharmaceutical occupations in Slovenian family names = Nomen est omen : medicinska i farmaceutska zanimanja u slovenskim prezimenima - Ramšak, Mojca (2020)
The heritage of Slovenian house names and surnames reflects, among others, the former medicine and pharmaceutical occupations, midwifery, and folk medicine practices, and besides that, also health status and illnesses of people. Surnames, which are especially strongly intertwined with family, local and social history, are closely related to folk medicine and magic. Unlike house names (vulgo), which are the usual nicknames for physical and mental characteristics and abilities, surnames denote medicals occupations and medicinal folk practice as such. According to the most recent data (as of January 1, 2020) of The Statistical Office of the Republic of Slovenia, at least 40 surnames reminiscent former medical or pharmaceutical professions. These newly discovered digital data in open access are precious for the history of medicine because they allow comparing surnames geographically, by frequency, and through the time.
Baština slovenskih kućnih imena i prezimena odražava, među ostalim, nekadašnja medicinska i farmaceutska zanimanja, primaljske te narodne medicinske prakse, a uz to i zdravstveno stanje te bolesti ljudi. Prezimena, koja su posebno snažno isprepletena s obiteljskom, lokalnom i društvenom poviješću, usko su povezana s narodnom medicinom i magijom. Za razliku od kućnih imena (vulgo), koja su uobičajeno nadimci za fizičke i mentalne karakteristike i sposobnosti, prezimena označavaju medicinska zanimanja i medicinsku narodnu praksu kao takvu. Prema najnovijim podacima (od 1. siječnja 2020.) Zavoda za statistiku Republike Slovenije, najmanje četrdeset prezimena podsjeća na bivše medicinske ili farmaceutske profesije. Ovi svima dostupni digitalni podaci dragocjeni su za povijest medicine jer omogućuju usporedbu prezimena geografski, po učestalosti i kroz vrijeme.
Bibliografske bilješke uz tekst ; bibliografija: 12 jed.
Summary ; Sažetak.
Keywords: Prezimena -- Narodna medicina -- Medicinsko zanimanje -- Farmacija; Slovenija